PENGENDALIAN PERSEDIAAN PUPUK DENGAN TEKNIK PPB (PART PERIOD BALANCING) (STUDI KASUS PT. PERKEBUNAN MILANO SEI DAUN DESA PENGARUNGAN KECAMATAN TORGAMBA KABUPATEN LABUHAN BATU SELATAN) - Pangaribuan, Jonner; Lumbantoruan, Ivan Rivaldi (UNIKA Santo Thomas, 2023)
This study aims to determine the optimal inventory and minimal costs with the PPB (Part Period Balancing) technique at PT. Perkebunan Milano Sei Daun Plantation, Pengarungan Village, Torgamba District, Labuhan Batu Selatan Regency in 2020. The research method used in this study is the documentation method in the form of ordering cost data, storage costs, and data about Lead Time (Waiting Time). The data analysis technique used is the PPB technique method, namely determining the amount of fertilizer inventory, determining ordering and storage costs, determining data on Lead Time and determining the number of economical orders per month (5 months).Based on the calculation of the results of the analysis of fertilizer supplies using the PPB (Part Period Balancing) technique, it was found that fertilizer orders were made according to the fertilizer needs to be used every month with the ability of the workforce in the company to sprinkle Super NPK fertilizer, so that the inventory became zero and there was a cost savings for holding fertilizer supplies. Super NPK. Based on the results of the analysis using the PPB technique, the waiting time (Lead Time) in planning for ordering Super NPK Fertilizer fertilizer orders can be made every mid-month starting from January - May, for ordering NPK Super fertilizer in July - November it can be done every mid-month according to their needs, so that fertilizer does not accumulate in the warehouse which causes fertilizer to petrify due to being stored for too long and the warehouse becomes full. Based on the analysis of the supply of NPK Super fertilizer with the PPB (Part Period Balancing) technique, if fertilizer orders are made every month with 5 orders starting from January - May the company will save storage costs to Rp 59,656,704 which was previously Rp 102,934,651, so the difference is Rp 43,368,947. The company also saves on inventory costs by Rp 135,712,855 which previously was Rp 178,990,810, so the difference is Rp 43,277,955. If the fertilizer order is ordered 5 times, starting in July - November the company will save storage costs of Rp. 67,656,294 which previously was Rp. 137,482,434, so the difference is Rp. 69,826,140. The company also saved inventory costs by Rp 193,531,745 from Rp 263,357,893, so the difference was Rp 69,826,148.